Bawaslu's Strategies for Preventing and Addressing Electoral Violations in the 2024 Election in Sinjai Regency - Sumardi Sumardi; Jusniaty Jusniaty; Muhammad Lutfi; Achmad Nurmandi (Universitas Muhammadiyah Tangerang, 2026)
This study examines the strategies employed by the Election Supervisory Board (Bawaslu) in preventing and addressing electoral violations during the 2024 Election in Sinjai Regency, Indonesia. The research focuses on assessing the effectiveness of these strategies in relation to local institutional constraints and socio-political dynamics. A qualitative approach was applied through in-depth interviews with key stakeholders, field observations, and analysis of official documents. The findings indicate that electoral violations are predominantly committed by bureaucratic actors, particularly civil servants (ASN), accounting for approximately 70% of cases, mainly involving breaches of neutrality. Preventive strategies including voter education, participatory monitoring, and electoral socialization have contributed to increasing public awareness and expanding oversight networks. However, their effectiveness remains limited, as reflected in three key indicators: low public reporting participation, weak follow-up consistency on reported cases, and limited deterrent effects of sanctions. Furthermore, enforcement practices tend to be administrative rather than punitive, with only a small proportion of cases meeting criminal thresholds. This enforcement asymmetry reduces the overall deterrence capacity of the supervisory system.This study contributes to the literature on electoral governance by demonstrating that, in decentralized contexts, the effectiveness of electoral oversight is shaped not only by institutional design but also by bureaucratic behavior, local political structures, and enforcement capacity. Strengthening crosssector collaboration, improving technical capacity, and adopting data-driven oversight mechanisms are therefore essential to enhance electoral integrity at the local level. Penelitian ini bertujuan untuk menganalisis strategi yang digunakan oleh Badan Pengawas Pemilihan Umum (Bawaslu) dalam mencegah dan menangani pelanggaran pemilu pada Pemilu Tahun 2024 di Kabupaten Sinjai, Indonesia. Fokus penelitian ini adalah menilai efektivitas strategi tersebut dalam konteks keterbatasan kelembagaan dan dinamika sosial-politik lokal. Pendekatan kualitatif digunakan melalui wawancara mendalam dengan informan kunci, observasi lapangan, serta analisis dokumen resmi. Hasil penelitian menunjukkan bahwa pelanggaran pemilu didominasi oleh aktor birokrasi, khususnya Aparatur Sipil Negara (ASN), yang mencakup sekitar 70% dari total kasus dan sebagian besar berkaitan dengan pelanggaran netralitas. Strategi pencegahan berupa pendidikan pemilih, pengawasan partisipatif, dan sosialisasi kepemiluan berkontribusi dalam meningkatkan kesadaran publik serta memperluas jejaring pengawasan. Namun demikian, efektivitasnya masih terbatas, yang tercermin dari rendahnya partisipasi pelaporan masyarakat, belum konsistennya tindak lanjut terhadap laporan pelanggaran, serta lemahnya efek jera dari sanksi yang diberikan. Selain itu, praktik penegakan hukum cenderung bersifat administratif dibandingkan represif, dengan hanya Sebagian kecil kasus yang memenuhi unsur tindak pidana. Ketimpangan dalam penegakan ini mengurangi daya cegah sistem pengawasan pemilu secara keseluruhan. Penelitian ini berkontribusi pada pengembangan kajian tata Kelola pemilu dengan menunjukkan bahwa dalam konteks desentralisasi, efektivitas pengawasan pemilu tidak hanya ditentukan oleh desain kelembagaan, tetapi juga oleh perilaku birokrasi, struktur politik lokal, serta kapasitas penegakan hukum. Oleh karena itu, penguatan kolaborasi lintas aktor, peningkatan kapasitas teknis, dan penerapan mekanisme pengawasan berbasis data menjadi langkah strategis untuk meningkatkan integritas pemilu di tingkat lokal.